Documentary film politics and the politics of documentary film - Lieza Louw (Communicare)
This paper sets out to consider the production of political documentary films in post-apartheid South Africa at a time when massification of the media and state capture of the South African Broadcasting Corporation, the country’s public broadcaster, silenced oppositional voices. Rehad Desai’s award-winning film, Miners Shot Down (2014) serves as the main case study for the research. The film deals with the days leading up to the final and tragic outcome of strike action by miners at a time when the print media predicated the state and the mine owners’ points of view. The filmmaker, a self-acclaimed political activist, set out to recount the events by recreating a voice for the mine workers by offering his personal reaction to the deaths of the 34 black men by interviews and archival material. Miners Shot Down was received well locally and internationally, but as an overt political narrative presented in a subjective reconstruction, some of the omissions may impact on a fuller understanding of the tragic event.tion. This finding prompted recommendations for entrepreneurs, policymakers and scholarship.